2010
DOI: 10.12927/hcq.2010.21963
|View full text |Cite
|
Sign up to set email alerts
|

National Analysis of Sepsis Hospitalizations and Factors Contributing to Sepsis In-Hospital Mortality in Canada

Abstract: Sepsis is one of the leading causes of in-hospital mortality in Canada. Patient safety is an important component of sepsis prevention and control. The Canadian Institute for Health Information recently released a report that examines a national picture of sepsis hospitalizations and mortality. This article highlights and expands some of the key findings from this report. Specifically, we look here more closely at patients admitted through the emergency departments (ED) in order to determine if earlier recognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 10 publications
3
61
0
1
Order By: Relevance
“…[3][4][5] A 2009 report published by the Canadian Institute for Health Information provided an alarming picture of an escalating number of cases of sepsis on a national level. 6 In 2008-2009, they reported over 30,000 cases of sepsis hospitalizations in Canada, an increase by almost 4,000 from 2005. Mortality rates continue to remain greater than 30% in Canada and are significantly higher than other critical conditions treated in the emergency department (ED), including myocardial infarction, trauma, and stroke.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] A 2009 report published by the Canadian Institute for Health Information provided an alarming picture of an escalating number of cases of sepsis on a national level. 6 In 2008-2009, they reported over 30,000 cases of sepsis hospitalizations in Canada, an increase by almost 4,000 from 2005. Mortality rates continue to remain greater than 30% in Canada and are significantly higher than other critical conditions treated in the emergency department (ED), including myocardial infarction, trauma, and stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In Canadian hospitals, sepsis is more common than cardiovascular disease, and has a higher fatality rate 1. In the United Kingdom, evidence from the National Health Service has recently shown that sepsis is responsible for more deaths annually than lung cancer, bowel cancer, and breast cancer 2.…”
Section: Introductionmentioning
confidence: 99%
“…EE might reinforce the intestinal barrier by this mechanism and prevent the important phase of sepsis, translocation of intestinal flora. Mortality and morbidity from sepsis is common, usually after liver and lung dysfunction that are related to multiple organ failure [27]. Liver dysfunction is commonly seen in sepsis patients [28].…”
Section: Journal Of Investigative Surgerymentioning
confidence: 99%